Radiation Hardness tests with neutron flux on different Silicon photomultiplier devices. (6th July 2017) - Cattaneo, P.W.; Cervi, T.; Menegolli, A.; Oddone, M.; Prata, M.; Prata, M.C.; Rossella, M.
Abstract: Radiation hardness is an important requirement for solid state readout devices operating in high radiation environments common in particle physics experiments. The MEG II experiment, at PSI, Switzerland, investigates the forbidden decay μ +  → e +  γ . Exploiting the most intense muon beam of the world. A significant flux of non-thermal neutrons (kinetic energy E k ⩾  0.5 MeV) is present in the experimental hall produced along the beam-line and in the hall itself. We present the effects of neutron fluxes comparable to the MEG II expected doses on several Silicon Photomultiplier (SiPMs). The tested models are: AdvanSiD ASD-NUV3S-P50 (used in MEG II experiment), AdvanSiD ASD-NUV3S-P40, AdvanSiD ASD-RGB3S-P40, Hamamatsu and Excelitas C30742-33-050-X. The neutron source is the thermal Sub-critical Multiplication complex (SM1) moderated with water, located at the University of Pavia (Italy). We report the change of SiPMs most important electric parameters: dark current, dark pulse frequency, gain, direct bias resistance, as a function of the integrated neutron fluency.